Research on Evaluation Index System of Equipment Support Capability - Jun Zhao, Sunqing Xu (Forest Chemicals Review, 2021)
Proceed from the equipment support capability evaluation, the paper hackles the prima-ry connotation of equipment support capability evaluation and illuminates object and content. Based on it, the paper conceives many objective evaluation index system particularly from equipment technical support capability, equipment adjustment and distribution support capability, equipment outlay sup-port capability and equipment management capability. It studies qualitative index, quantitative index, index consistency and weight disposal method.